2018
DOI: 10.1177/0897190018760622
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Correlates of Health-Related Quality of Life in Patients With Type 2 Diabetes Mellitus

Abstract: The study demonstrated that patients with T2DM with MetS have overall poor HRQOL as compared to patients with T2DM without MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Lack of freedom to eat the food of choice was implicated as a cause for poor QOL in people living with diabetes from Karnataka, India [11]. The presence of MetS, central obesity has been linked with poorer QOL in people living with T2DM from Punjab India [13].…”
Section: Aementioning
confidence: 99%
“…Lack of freedom to eat the food of choice was implicated as a cause for poor QOL in people living with diabetes from Karnataka, India [11]. The presence of MetS, central obesity has been linked with poorer QOL in people living with T2DM from Punjab India [13].…”
Section: Aementioning
confidence: 99%
“…Studies conducted so far have reported that quality of life decreases with the presence of complications 25,26,28,29,30,31,32 . Quality of life in individuals with type 2 diabetes varies depending on complications, presence of other diseases, and the duration of the disease 33,34,35 . In our study, 70% of the individuals with diabetes had an additional chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 41 reviewed studies, only two assessed QoL among T2D patients with comorbidities[ 24 ] or metabolic syndrome. [ 56 ] A stroke had a high negative impact on the physical HRQoL. The presence of comorbidities affected the physical component summary (PCS) and the mental component summary (MCS) of the Short Form Health Survey-12.…”
Section: R Esultsmentioning
confidence: 99%
“…[ 24 ] Among T2D diabetes patients with metabolic syndrome, a greater significant decline is observed in PCS and MCS as compared to those without metabolic syndrome. [ 56 ]…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation